Evaluation on physicochemical properties of iso-butanol additives in ethanol-gasoline blend on performance and emission characteristics of a spark-ignition engine. (5th November 2018) - Zaharin, M.S.M.; Abdullah, N.R.; Masjuki, H.H.; Ali, Obed M.; Najafi, G.; Yusaf, Talal
Highlights: Complete combustion achieved with Iso-butanol additive in ethanol-gasoline blend. E10B15 producing the highest maximum brake power with 68.93 kW. E10B15 exhibits the lowest fuel consumption of 315.17 g/kWh at a speed of 5000 rpm. The brake thermal efficiency increased by 27.35% for E10B15 compared to PG. The emissions of CO and HC have been reduced with alcohol-gasoline blended fuel. Abstract: In this study, experiments were conducted on a four-cylinder spark-ignition engine to investigate the effects of iso-butanol additives in ethanol-gasoline blend on fuel properties, performance and emission characteristics of a SI engine. The engine tests were carried out at 50% wide open throttle and variations of engine speed from 3000 to 5000 RPM with an interval of 1000 RPM. The engine was fueled with base gasoline fuel, ethanol-gasoline blended fuel at 10% volume percentage of ethanol (E10) and three different fuel blends of iso-butanol additives; 5%, 10% and 15%, in E10 blended fuel denoted as E10B5, E10B10 and E10B15, respectively. Physicochemical properties tests were conducted in this study to evaluate the fuel heating value, kinematic viscosity and density, which have been selected due to their influences on engine performance and exhaust emissions. Results of heating value showed a decreasing pattern for the blended fuel samples compared with that of base gasoline fuel as E10, E10B5, E10B10 and E10B15 produced 2.33%, 3.14%, 5.06%, and 5.31%, respectively. However, as alcohol concentration increases in the blended fuel samples, the density and kinematic viscosity were both increased with maximum values of 0.767 g/cm 3 and 1.15 mm 2 /s, respectively obtained for E10B15. In terms of engine performance, the blended fuel samples exhibited higher brake power than that of base gasoline fuel with mean increase of 7.71%, 10.21%, 10.89% and 11.54% for E10, E10B5, E10B10 and E10B15, respectively. Significant reduction in brake specific fuel consumption obtained with E10, E10B5, E10B10 and E10B15 by mean of 3.57%, 5.15%, 7.14% and 10.89% respectively, compared to base gasoline fuel. Noticeable improvement of brake thermal efficiency observed with the blended fuel at a maximum increment of 18.91% achieved by E10B15. High combustion temperature produced by the blended fuel samples have been contributed to the higher exhaust gas temperature. Accordingly, the emissions of carbon monoxide and hydrocarbon were all reduced; except for carbon dioxide and nitrogen oxide, with the addition of iso-butanol additive compared to those of ethanol-gasoline blend and base gasoline fuel.